2018
DOI: 10.4184/asj.2018.12.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Paraspinal Muscle Atrophy Percentage after Minimally Invasive Transforaminal Lumbar Interbody Fusion and Unilateral Instrumentation Using a Novel Contralateral Intact Muscle-Controlled Model

Abstract: Study DesignRetrospective comparative clinical study.PurposeThis study aimed to assess paraspinal muscle atrophy in patients who underwent minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) and unilateral pedicle screw fixation using a novel contralateral intact muscle-controlled model.Overview of LiteratureThe increased incidence of paravertebral lumbar muscle injuries after open techniques has raised the importance of implementing minimally invasive spine surgical techniques using tubular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…PVM degeneration is characterized by increased fat infiltration and decreased muscle volume (11). PVM degeneration is associated with various lumbar diseases and post-operative complications (12,13). It was reported that the degree of fat infiltration and atrophy of the multifidus is closely linked to the severity of lower back pain (LBP) (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…PVM degeneration is characterized by increased fat infiltration and decreased muscle volume (11). PVM degeneration is associated with various lumbar diseases and post-operative complications (12,13). It was reported that the degree of fat infiltration and atrophy of the multifidus is closely linked to the severity of lower back pain (LBP) (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…There was no significant change in the psoas muscle [ 26 ]. Ortega-Porcayo et al [ 27 ] found that when they performed minimally invasive transforaminal lumbar interbody fusion on one side with unilateral pedicle screw instrumentation, there was no significant difference between the surgical and the non-surgical sides. Our finding echoes the study by Ortega-Porcayo et al [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PVM play a crucial role in the stability and motor function of the lumbar spine and are associated with various lumbar spine diseases and postoperative complications [ 18 , 19 ]. The MF is sensitive to pathological changes and is the muscle that shows the most obvious and most common degeneration among the lumbar PVM [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%